Constraining Latent and Sensible Heat Fluxes during Drifting and Blowing Snow Events in Antarctica using in–situ Measurements and Large–Eddy Simulations - Sigmund, Armin; Huwald, Hendrik; Gerber, Franziska; Dujardin, Jérôme; Comola, Francesco; Sharma, Varun; Brito Melo, Daniela; Lehning, Michael (2023)
Reliable predictions of sea level rise require a quantitative understanding of the mass balance of the Antarctic ice sheet. Water vapor exchange between snow and the atmospheric boundary layer may be an important term in the mass balance equation but current estimates for this process are highly uncertain. The exchange of water vapor becomes particularly strong during drifting and blowing snow events, which are frequent in Antarctica. In these conditions, measured turbulent ﬂuxes based on the Eddy–Covariance (EC) method or the Monin–Obukhov (MO) bulk formula are associated with increased uncertainties that are diﬃcult to quantify. The EC raw data can contain artifacts because blowing snow particles temporarily perturb the measurement signals of ultrasonic anemometers and open–path infrared gas analyzers. The MO bulk approach suﬀers from the fact that sources or sinks of moisture and heat in the drifting and blowing snow layer violate the assumption of height–constant ﬂuxes. Additionally, strong winds typically result in small vertical diﬀerences in temperature and humidity, which makes the MO bulk approach particularly sensitive to instrument–speciﬁc biases in temperature and humidity. In view of these limitations, it is difficult to validate models, especially the parametrizations used in large-scale models. Nevertheless, detailed small-scale numerical simulations can help to constrain vapor and heat exchange and to disentangle diﬀerent sources of uncertainty. In this study, we use Large-Eddy Simulations (LES) as a reference to validate and improve parametrizations of latent and sensible heat fluxes in conditions of drifting and blowing snow. The boundary conditions of the LES simulations are based on field measurements at the Japanese Syowa S17 Station, coastal East Antarctica. Consistent with the almost flat and permanently snow-covered terrain, the LES simulations assume a flat snow surface a the lower boundary of the domain (approximately 38 x 19 x 18 m^3). The transport of snow particles and their ...